Probiotic properties of Debaryomyces hansenii BCS004 and their immunostimulatory effect in supplemented diets for gilthead seabream (Sparus aurata). (1st February 2021) - Reyes‐Becerril, Martha; Angulo, Carlos; Angulo, Miriam; Esteban, María Ángeles
Abstract: Debaryomyces hansenii BCS004 strain is a non‐pathogenic, polyamine and superoxide dismutase secreting marine yeast. The objective of this study was to investigate the marine yeast DhBCS004 as probiotics and evaluate its antimicrobial properties and dietary immunostimulant effect on gilthead seabream specimens when administered at 10 6 colony‐forming unit/g −1 or 1.1% for 4 weeks. This yeast strain showed potential probiotic properties, including stability in gastrointestinal survival (pH, bile conditions) and attachment to intestinal cells. The DhBCS004 had antimicrobial activity against important marine pathogens. Interestingly, this yeast has a high amount of n−3 polyunsaturated fatty acids with high concentrations of oleic and linoleic acids, which may confer nutritional and therapeutic values. The in vivo immunological assay revealed that dietary DhBCS004 significantly increased phagocytosis capacity, peroxidase and respiratory burst activities in leucocytes. Furthermore, the natural haemolytic complement activity and total IgM levels increased in serum after weeks 2 or 4 of trial. Finally, DhBCS004 significantly increased the transcriptions of TNF‐α, C3 and IgM in intestine samples. This work reinforces the biotechnological and immunological potential of D. hansenii BCS004 in the field of fish aquaculture.